Chronic cranial window for photoacoustic imaging: a mini review - Wang, Yongchao (Vis Comput Ind Biomed Art, 2021)
Photoacoustic (PA) microscopy is being increasingly used to visualize the microcirculation of the brain cortex at the micron level in living rodents. By combining it with long-term cranial window techniques, vasculature can be monitored over a period of days extending to months through a field of view. To fulfill the requirements of long-term in vivo PA imaging, the cranial window must involve a simple and rapid surgical procedure, biological compatibility, and sufficient optical-acoustic transparency, which are major challenges. Recently, several cranial window techniques have been reported for longitudinal PA imaging. Here, the development of chronic cranial windows for PA imaging is reviewed and its technical details are discussed, including window installation, imaging quality, and longitudinal stability.